Spontaneous periodic ordering on the surface and in the bulk of dielectrics irradiated by ultrafast laser: a shared electromagnetic origin - Rudenko, Anton (Sci Rep, 2017)
Periodic self-organization of matter beyond the diffraction limit is a puzzling phenomenon, typical both for surface and bulk ultrashort laser processing. Here we compare the mechanisms of periodic nanostructure formation on the surface and in the bulk of fused silica. We show that volume nanogratings and surface nanoripples having subwavelength periodicity and oriented perpendicular to the laser polarization share the same electromagnetic origin. The nanostructure orientation is defined by the near-field local enhancement in the vicinity of the inhomogeneous scattering centers. The periodicity is attributed to the coherent superposition of the waves scattered at inhomogeneities. Numerical calculations also support the multipulse accumulation nature of nanogratings formation on the surface and inside fused silica. Laser surface processing by multiple laser pulses promotes the transition from the high spatial frequency perpendicularly oriented nanoripples to the low spatial frequency ripples, parallel or perpendicular to the laser polarization. The latter structures also share the electromagnetic origin, but are related to the incident field interference with the scattered far-field of rough non-metallic or transiently metallic surfaces. The characteristic ripple appearances are predicted by combined electromagnetic and thermo-mechanical approaches and supported by SEM images of the final surface morphology and by time-resolved pump-probe diffraction measurements.